Fabrication of Nanostructured Coatings - Singh, Harminder (Asian Review of Mechanical Engineering, 2016)
The outstanding thermal, mechanical, electrical and electronic properties of nanocrystalline materials and carbon nanotubes hasattracted considerable research interests, and is now one of the major identifiable activities for material scientists. However, the practical and commercial use of these materials requires efficient processing methods, which needs to be compatible with the existing processes. One of the problems limiting their application is preparation of these materials. Currently, these materials have been prepared in the laboratory by traditional method of compacting the metallic powders which consist of particles at nanoscale. This method has many limitations to achieve properties required at nanoscale. The development of surface nanostructured coatings has been considered as potential industrial application. The nanostructured coatings can be formed by various methods such as physical vapour deposition (PVD), sputtering, chemical vapour deposition (CVD), electrochemical deposition, electrospark deposition. This study has reviewed the formation of nanocoatings by different processes, with emphasis on embedding carbon nanotubes in coating structure.